Web scale discovery - giải pháp tìm kiếm và khai thác thông tin cho các thư viện trong kỷ nguyên Internet - Đỗ, Văn Hùng (Cục Thông tin khoa học và công nghệ quốc gia, 2023)
Web scale discovery (WSD) is the emerging activity of libraries operating in the online environment and consisting of different fragmented databases. The article explains the emergence of the Web Scale Discovery WSD, provides the basic definition and structure of the system as well as suggestions of how to develop and apply this system into Vietnamese libraries (especially university libraries).